2017
DOI: 10.1002/sctm.17-0148
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Bioprinting of Stem Cells for Transplantable Tissue Fabrication

Abstract: Bioprinting is a quickly progressing technology, which holds the potential to generate replacement tissues and organs. Stem cells offer several advantages over differentiated cells for use as starting materials, including the potential for autologous tissue and differentiation into multiple cell lines. The three most commonly used stem cells are embryonic, induced pluripotent, and adult stem cells. Cells are combined with various natural and synthetic materials to form bioinks, which are used to fabricate scaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
94
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(98 citation statements)
references
References 82 publications
0
94
0
2
Order By: Relevance
“…Perhaps due to the urgent nature of this clinical condition, the application of 3D bioprinting in the cardiovascular domain has seen rapid progress in recent years. Several animal studies have already shown that 3D bioprinted cardiac patches have the ability to reduce fibrosis, hypertrophy, and infarct extent [70][71][72][73][74][75]. The impact will extend beyond transplantation to include disease modeling and drug studies, as we have seen for other tissues such as skin.…”
Section: Cardiovascular Tissuementioning
confidence: 95%
“…Perhaps due to the urgent nature of this clinical condition, the application of 3D bioprinting in the cardiovascular domain has seen rapid progress in recent years. Several animal studies have already shown that 3D bioprinted cardiac patches have the ability to reduce fibrosis, hypertrophy, and infarct extent [70][71][72][73][74][75]. The impact will extend beyond transplantation to include disease modeling and drug studies, as we have seen for other tissues such as skin.…”
Section: Cardiovascular Tissuementioning
confidence: 95%
“…However, many challenges must be overcome before bioprinting technology is used routinely in a clinical setting (Leberfinger et al, 2017).…”
Section: Advanced Scaffold Production Techniques Electrospinning Of Nmentioning
confidence: 99%
“…Many exciting advances in the use of bioactive components for precision medicine have already been implemented in clinical settings for non‐3D printing applications, such as personalized gene therapies or matrix‐induced autologous chondrocyte implantation . Further, advances in gene therapy, cell culture, and cell manufacturing offer an array of exciting new components to incorporate into bioinks for precision medicine . While not the focus of this progress report, design of these inks, which can be broken into further discrete unit operators, has been detailed in previous reviews …”
Section: Introductionmentioning
confidence: 99%
“…While ease of analysis and access to patient data has improved for clinicians, many limitations still exist for the translation of precision medicine to patient treatment, including prohibitive costs, poor or nonexistent manufacturing www.advmat.de www.advancedsciencenews.com in gene therapy, cell culture, and cell manufacturing offer an array of exciting new components to incorporate into bioinks for precision medicine. [16,[23][24][25][26][27] While not the focus of this progress report, design of these inks, which can be broken into further discrete unit operators, has been detailed in previous reviews. [2,3,5,28] The next step in the process uses these inks to fabricate the constructs designed in the first step ( Figure 1C).…”
Section: Introductionmentioning
confidence: 99%